Mapping Critical Thinking Skills through Newman’s Error Analysis in Secondary Students’ Problem-Solving - Hariri, Dewi Damayanti; Kania, Nia (FKIP Universitas Lampung, 2025)
Mathematics plays a crucial role in fostering students’ logical, critical, and analytical thinking skills. However, many students still face challenges in understanding and applying mathematical concepts. This study aims to map students' critical thinking skills through an analysis of student errors in solving problems involving systems of linear equations in three variables using Newman Error Analysis (NEA). The research was conducted using a qualitative descriptive approach, supported by written tests and interviews. The research sample was 33 eleventh-grade high school students in Majalengka Regency, West Java. The findings revealed that while no errors occurred at the reading stage, 48% of students made comprehension errors, 57% made transformation errors, 66% experienced process skill errors, and 82% committed encoding errors. The most dominant errors were encoding errors, reflecting weaknesses in the aspects of evaluating evidence and drawing conclusions. Most encoding errors were influenced by students' lack of confidence and learning motivation. These results suggest that difficulties in earlier stages of problem-solving significantly affect students’ ability to arrive at correct final answers. The study emphasizes the importance of strengthening students’ procedural fluency and supporting their cognitive processes to improve mathematical problem-solving performance. Keywords: contextual, critical thinking skills, Newman’s error analysis, three-variable linear equation.